Economic Policy Coordination : Proceedings of an International Seminar held in Hamburg - Guth, Wilfried (International Monetary Fund, 1988)
This volume, which presents the proceedings of a seminar moderated by Wilfred Guth in Hamburg, Germany, dicusses the extent of international policy coordination, its effectiveness, and how it can be expected to work in the future.